If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x = 3 + -4x + 6 Reorder the terms: -1x = 3 + 6 + -4x Combine like terms: 3 + 6 = 9 -1x = 9 + -4x Solving -1x = 9 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -1x + 4x = 9 + -4x + 4x Combine like terms: -1x + 4x = 3x 3x = 9 + -4x + 4x Combine like terms: -4x + 4x = 0 3x = 9 + 0 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 13x^2-(3x^2+2x)-(-6)= | | A=1020(1-0.195)20 | | (x^2)-6x+18=0 | | 12x+6=5x+4 | | 18b+8=b-689 | | 5v^2-13=0 | | 8(300+-1.5y)+12y=2400 | | x+1=18x-10 | | 2+2x+6=6+5+2+x | | y-207=-7y-7 | | 1.2m-8=-2.0m | | 3x+8y+5z=27 | | (x^2)+11x+30=0 | | 2x+10i=-16-2yi | | 3h=1.5 | | Y=20(0.682)x | | 17+-2z=13 | | n-.3n=200 | | 3x+2y-7=0 | | 6y-7=5y+1 | | x+3+6+6=3+4x | | 13x-15x+8=4+2-24 | | -d-16=26 | | 2(2y-16)=0 | | -49-9x=-202 | | -w-9=15 | | -3a+3a+6=7 | | 1.3n=200 | | b-140=7b-8 | | Y=20(1.025)x | | 2(a-5)+4=a+9 | | 8y-12-6y=6y+6 |